Impaired myocardial development resulting in neonatal cardiac hypoplasia alters postnatal growth and stress response in the heart. (6th February 2015) - Drenckhahn, Jörg-Detlef; Strasen, Jette; Heinecke, Kirsten; Langner, Patrick; Yin, Kom Voy; Skole, Friederike; Hennig, Maria; Spallek, Bastian; Fischer, Robert; Blaschke, Florian; Heuser, Arnd; Cox, Timothy C.; et al.
Abstract: Aims: Foetal growth has been proposed to influence cardiovascular health in adulthood, a process referred to as foetal programming. Indeed, intrauterine growth restriction in animal models alters heart size and cardiomyocyte number in the perinatal period, yet the consequences for the adult or challenged heart are largely unknown. The aim of this study was to elucidate postnatal myocardial growth pattern, left ventricular function, and stress response in the adult heart after neonatal cardiac hypoplasia in mice. Methods and results: Utilizing a new mouse model of impaired cardiac development leading to fully functional but hypoplastic hearts at birth, we show that myocardial mass is normalized until early adulthood by accelerated physiological cardiomyocyte hypertrophy. Compensatory hypertrophy, however, cannot be maintained upon ageing, resulting in reduced organ size without maladaptive myocardial remodelling. Angiotensin II stress revealed aberrant cardiomyocyte growth kinetics in adult hearts after neonatal hypoplasia compared with normally developed controls, characterized by reversible overshooting hypertrophy. This exaggerated growth mainly depends on STAT3, whose inhibition during angiotensin II treatment reduces left ventricular mass in both groups but causes contractile dysfunction in developmentally impaired hearts only. Whereas JAK/STAT3 inhibition reduces cardiomyocyte cross-sectional area in the latter, it prevents fibrosis in control hearts, indicating fundamentally different mechanisms of action. Conclusion: Impaired prenatal development leading to neonatal cardiac hypoplasia alters postnatal cardiac growth and stress response in vivo, thereby linking foetal programming to organ size control in the heart.